De la solidaridad socialista al multilateralismo contemporáneo: Cuba entre el CAME y los BRICS - Allende Sopelana, Itsasne (El Colegio de México A.C., 2025)
This article analyzes Cuba’s trajectory from its participation in the Council for Mutual Economic Assistance (CAME in Spanish), as part of the socialist bloc, to its current interest in the BRICS, a forum of emerging economies that combines economic pragmatism with a multilateral cooperation agenda. It examines the transformations in Cuba’s integration strategy following the collapse of the Soviet Union, as well as the challenges and opportunities posed by its inclusion in the BRICS. Although the approach of this bloc differs from the solidarity-based model of the CAME, its integration offers Cuba a platform to strengthen its South-South cooperation and diversify its international relations. The success of this participation will depend on the island’s ability to harmonize its ideological legacy with the dynamics and demands of a transforming international system, positioning itself as a relevant actor in the emerging multipolar order.